Effect of Voltage Bias at MEH-PPV Layer on SPR Wavelength observed during in-situ Measurement Method in Polymer Light Emitting Diode - Hendro Hendro; Mitra Djamal; Rahmat Hidayat; Daniel Kurnia; Buchari Buchari (Institut Teknologi Bandung, 2011)
The shifting of surface plasmon resonance (SPR) wavelength has been observed during in situ measurement in polymer light emitting diode (pLED). Examination is performed using an pLED sample which has an ITO/PEDOT:PSS/MEH-PPV/Au structure. When the voltage bias is increased from 0 to 9 volt the SPR wavelength shifts from 612 nm to 628 nm and the absorption curve shifts to lower absorbance value. From the theoretical analysis, it can be understood that the change of the SPR dip and the absorption curves correspond to the change of dielectric constant of the MEH-PPV layer. These results show that SPR wavelength depends on the metal and air dielectric constant as well as on the MEH-PPV layer. These results also imply that the SPR wavelength being evaluated can be controlled by varying the voltage bias.